Association between life satisfaction and fall severity among hospitalized stroke patients - Xuhui Li; Qingfang Zhang; Jie Yan; Yulong Wang; Jianjun Long; Xing Lv; Miaoling Chen; Wensheng Chen (Scientific Reports)
Abstract Falls are common during stroke rehabilitation, leading to physical injuries and psychosocial consequences. While prior studies have explored the association between falls and life satisfaction, the effect of fall-related injury severity remains unclear. This multicenter cross-sectional study included 6,068 stroke inpatients undergoing rehabilitation. Standardized face-to-face interviews were conducted to collect data on fall experiences within the past three months, severity of fall-related injuries, life satisfaction, and other demographic and clinical characteristics. Logistic regression models were used to analyze the relationships between fall experiences, injury severity, and life satisfaction. After adjusting for confounding factors such as age, sex, and activities of daily living, patients who had experienced a fall in the past three months exhibited significantly lower life satisfaction (OR = 0.77, 95% CI: 0.61–0.98, P = 0.0325). However, no significant association was observed between the severity of fall-related injuries and life satisfaction (P > 0.05). These findings highlight the need for fall prevention and psychosocial support in stroke rehabilitation to improve well-being. Future research should explore the mechanisms linking fall-related injuries and life satisfaction to refine rehabilitation strategies.